Is there a space for medium-sized cassava seed growers in Nigeria? - Bentley, J.W.; Nitturkar, H.; Obisesan, D.; Friedmann, M.; Thiele, Graham (Informa UK Limited, 2020)
Until recently, there has been little commercial sale of vegetatively propagated crop seed, except for potatoes (Solanum tuberosum). This is especially true in developing countries. However, a formal, commercial seed sector for cassava (Manihot esculenta) is emerging in Nigeria. In 2016, a project, Building an Economically Sustainable Integrated Cassava Seed System in Nigeria (BASICS), started to encourage village farmers to certify and sell cassava seed. A questionnaire survey of 30 cassava entrepreneurs across Nigeria in 2019 included some of those village-based growers as well as larger producers, including some who certified their planting material. In the long run, if there is a consistent demand for certified cassava seed, medium-sized producers may be able to satisfy some of that demand, especially if they have continued programmatic support; otherwise, these budding seed entrepreneurs may close down.